Resistance training as a tool for changing muscle mass and frailty status in sarcopenic older women: a quasi-experimental study - Joana Ude Viana; João Marcos Domingues Dias; Leani Souza Máximo Pereira; Silvia Lanziotti Azevedo da Silva; Rosângela Corrêa Dias; Lygia Paccini Lustosa (in memoriam) (Universidade de São Paulo, 2022)
ABSTRACT Frailty and sarcopenia are geriatric syndromes highly prevalent, complex, and hard to diagnose and treat. The literature still lacks a consensus on which resistance training program is better for older people, especially when considering frailty status and sarcopenia. We aimed to evaluate the effectiveness of a progressive resistance training program on muscle mass and frailty status in older sarcopenic women. This study included 18 community-dwelling sarcopenic women aged 65 or older enrolled in the progressive resistance training program. The intervention was based on 75% of each subject's maximum repetition test (3 times/week, for 12 weeks). Before the intervention, 16.7% were frail, and 61.1% were pre-frail; after the intervention, 5.6% were frail, and 50% were pre-frail. The result shows that the intervention reduced frailty status and increased muscle mass (p=0.01). Hence, after the intervention, we observed both a decrease in frailty and a positive change in function, since the percentage of robust women increased twice (p=0.01). We conclude that the progressive resistance training program might be the best strategy to prevent frailty and sarcopenia. Therefore, we suggest using weight resistance training in daily clinical practice to improve muscle mass and decrease frailty status in sarcopenic women.